Four 3D Cd(II)-based metal organic hybrids with different N,N `-donor spacers: syntheses, characterizations, and selective gas adsorption properties - Bhattacharya, Biswajit; Dey, Rajdip; Pachfule, Pradip; Banerjee, Rahul; Ghoshal, Debajyoti (Crystal Growth & Design, 2013)
{Four new metal organic frameworks with bivalent cadmium, disodium succinate (Na(2)suc), and four different N,N'-donor ligands, i.e., {[Cd(L1)(suc)]center dot(H2O)(3)}(n) (1), {[Cd(L2)(suc)]center dot(H2O)(2)\

Flexible dicarboxylate based pillar-layer metal organic frameworks: differences in structure and porosity by tuning the pyridyl based N, N ` linkers - Dey, Rajdip; Bhattacharya, Biswajit; Pachfule, Pradip; Banerjee, Rahul; Ghoshal, Debajyoti (CrystEngComm, 2014)
{Dicarboxylate supported metal organic hybrids of Co(II), Zn(II) and Cd(II) have been synthesized using two different pyridyl based N, N' linkers having Schiff base functionalized site. The use of flexible dicarboxylate glutarate in designing such frameworks has created a marked diversity in topology. The different N, N' donor linkers also played an active part in the channel modification in the synthesized MOFs. The structural and topological diversity has been analyzed from the single crystal X-ray structure. Five compounds, {[Co(azpy)(glut)]center dot(CH3OH)}(n) (1), {[Co(meazpy)(glut)(H2O)(2)]center dot (H2O)(3)

Syntheses, X-ray structures, catalytic activity and magnetic properties of two new coordination polymers of Co(II) and Ni(II) based on benzenedicarboxylate and linear N,N `-donor Schiff base linkers - Bhattacharya, Biswajit; Maity, Dilip Kumar; Pachfule, Pradip; Colacio, Enrique; Ghoshal, Debajyoti (Inorganic Chemistry Frontiers, 2014)
{Two isostructural coordination polymers based on Co(II) and Ni(II), {[M(azpy)(3)(p-bdc)(2)(H2O)(4)]center dot(CH3OH)(2)(H2O)(3)}(n) [where M = Co (1) and Ni (2); azpy = N,N'-bis-pyridin-4-ylmethylene-hydrazine and p-bdc = 1,4-benzenedicarboxylate], have been synthesized using mixed ligand systems at room temperature and characterized by single-crystal X-ray diffraction and other physicochemical methods. Structure determination reveals that both the complexes crystallize in the monoclinic space group C2/c and exhibit one-dimensional (1D) ladder like structures constructed by p-bdc and azpy ligands in which Schiff base (azpy) linkers serve as a bridging as well as pendent ligands. These pendent ligands are involved in H-bonding and pi-pi interactions with lattice water, methanol molecules and bridging azpy ligands, to form the 3D supramolecular structure. Notably, both the frameworks efficiently catalyze the Knoevenagel condensation reactions of a wide range of substituted benzaldehydes with active methylene compounds in heterogeneous medium under environmentally friendly conditions and the products were obtained in excellent yields. These catalysts were also found to exhibit excellent recyclability and re-usability without any significant loss of activity. A variable temperature magnetic study of both compounds was carried out and their magnetic properties justified on the basis of their crystal structure.